Tundra shrub ring widths in microns, North Slope Alaska 1965-2013 - Diane Huebner (Arctic Data Center, 2022)
Thermokarst disturbance in permafrost landscapes is likely to increase across the tundra biome with climate warming, resulting in changes to topography, vegetation, and biogeochemical cycling. Tundra shrubs grow on permafrost, but shrub - thermokarst relationships are rarely studied in detail. Since the 1980’s, Alaska’s North Slope has experienced increased thermokarst activity, including retrogressive thaw slumps (RTS) on hillslopes. Within decades, RTSs near Toolik Lake, Alaska, were colonized by tall (≥ 0.5 meters (m)) deciduous shrubs. We used dendrochronology methods on 66 shrubs (182 stem cross sections) representing dominant deciduous species: willows (Salix pulchra and Salix glauca) and dwarf birch (Betula nana) at two RTS chronosequences on Alaska’s North Slope comprising seven sites, to quantify thermokarst and climate effects (25 years of temperature and precipitation records) on shrub secondary growth (i.e., annual rings) in RTS-disturbed and undisturbed moist acidic tussock (MAT) tundra. Across species, average growth ring widths were 2 x wider for shrubs in RTSs than in MAT, and ring widths decreased with RTS age. A 1 degree Celsius (°C) June temperature increase was associated with 2% wider rings across species and sites, but shrubs showed marginal growth in warmer summers, supporting tundra-wide shrub climate sensitivity studies. A 4.5% average ring width increase per 1 mm of previous year’s September precipitation was seen in shrubs in mid-successional RTSs, suggesting protective effects of early snowfall in RTSs versus open tundra. RTS age category explained 47% and 30% of average ring width variance of willows and dwarf birch, respectively, in linear mixed effects models. Climate variables explained 2% average ring width variance across species. Our results suggest that RTS exert strong successional effects on tundra shrub growth. Climate effects appear to show weaker synoptic patterns across the study area. RTS will likely contribute to tundra greening where RTS activity is increasing.